Composition design and electrical properties of (K0.48Na0.52)NbO3-xLiSbO3}-y{(Bi0.5Na0.5)(Zr1-zSnz)O3} ceramics. (15th December 2017) - Liu, Wenfeng; Cheng, Lu; Gao, Jinghui; Wang, Ziwei; Li, Shengtao
Highlight: A new KNN ceramics system with Tc from 158 °C to 317 °C and multi-phase coexistence at room temperature. Large electrostrain with d 33 * of 675 pm/V which even rival that of 250 pm/V from hard-PZT ceramics. Large d 33 of 249 pC/N, the large planar coupling factor k p of 37.3% and high Curie temperature of 271 °C were achieved. Graphical abstract: Abstract: In the present study, we designed a new system, (K0.48 Na0.52 )NbO3 - x LiSbO3 }- y {(Bi0.5 Na0.5 )(Zr1 - z Sn z )O3 } and systemically investigated both the piezoelectric performance under weak field and the electrostrain under large electric field. Here the isovalent additive LiSbO3 (LS) was employed to pinch the three ferroelectric phases together, while the aliovalent dopant (Bi0.5 Na0.5 )(Zr0.8 Sn0.2 )O3 (BNZS) was introduced to further lower the Curie temperature ( T c ). The enhanced piezoelectric properties were achieved by pinching the phases with different symmetries together; hereinto the ceramic with LS content of 0.05 and BNZS content of 0.03 exhibited large piezoelectric coefficient ( d 33 ) of 249pC/N. Besides the high piezoelectric performance under weak field, the present ceramics also exhibited large electrostrain under large electric field, ascribing to the Zr 4 + and Sn 4 + in BNZS. The electrostrain reached 0.27% under the electric field of 4 kV/mm (with the converse piezoelectric coefficient d 33 * of 675 pm/V), even superior to the widely used hard PZT.